Soil coverage evolution and wind erosion risk on summer crops under contrasting tillage systems - Mendez, Mariano Javier (2015)
The effectiveness of wind erosion control by soil surface conditions and crop and weed canopy has been well studied in wind tunnel experiments. The aim of this study is to assess the combined effects of these variables under field conditions. Soil surface conditions, crop and weed coverage, plant residue, and non-erodible aggregates (NEA) were measured in the field between the fallow start and the growth period of sunflower (Helianthus annuus) and corn (Zea mays). Both crops were planted on a sandy-loam Entic Haplustoll with conventional-(CT), vertical-(VT) and no-till (NT) tillage systems. Wind erosion was estimated by means of the spreadsheet version the Revised Wind Erosion Equation and the soil coverage was measured each 15days. Results indicated that wind erosion was mostly negligible in NT, exceeding the tolerable levels (estimated between 300 and 1400kgha-1year-1 by Verheijen et al. (2009)) only in an year with high climatic erosivity. Wind erosion exceeded the tolerable levels in most cases in CT and VT, reaching values of 17,400kgha-1. Wind erosion was 2-10 times higher after planting of both crops than during fallows. During the fallows, the soil was mostly well covered with plant residues and NEA in CT and VT and with residues and weeds in NT. High wind erosion amounts occurring 30days after planting in all tillage systems were produced by the destruction of coarse aggregates and the burying of plant residues during planting operations and rains. Differences in soil protection after planting were given by residues of previous crops and growing weeds. The growth of weeds 2-4weeks after crop planting contributed to reduce wind erosion without impacting in crops yields. An accurate weeds management in semiarid lands can contribute significantly to control wind erosion. More field studies are needed in order to develop management strategies to reduce wind erosion.